2009
DOI: 10.1111/j.1540-6261.2008.01428.x
|View full text |Cite
|
Sign up to set email alerts
|

It's SHO Time! Short‐Sale Price Tests and Market Quality

Abstract: We examine the effects of the Securities and Exchange Commission (SEC)-mandated temporary suspension of short-sale price tests for a set of Pilot securities. While shortselling activity increases both for NYSE-and Nasdaq-listed Pilot stocks, returns and volatility at the daily level are unaffected. NYSE-listed Pilot stocks experience more symmetric trading patterns and a slight increase in spreads and intraday volatility after the suspension while there is a smaller effect on market quality for Nasdaqlisted Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
152
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(166 citation statements)
references
References 31 publications
(53 reference statements)
14
152
0
Order By: Relevance
“…Contrasting examples are the relaxation by the Securities and Exchange Commission of the uptick rule restricting short sales (Diether, Lee, and Werner 2009a;Jakab 2008) and recent efforts to constrain short selling described in note 1. Greater ease of short selling may potentially help protect investors from the hazards of trading overpriced stocks.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting examples are the relaxation by the Securities and Exchange Commission of the uptick rule restricting short sales (Diether, Lee, and Werner 2009a;Jakab 2008) and recent efforts to constrain short selling described in note 1. Greater ease of short selling may potentially help protect investors from the hazards of trading overpriced stocks.…”
Section: Discussionmentioning
confidence: 99%
“…The relaxation by the Security and Exchange Commission of the "uptick rule" restricting short sales is a possible example Werner 2009b, andJakab 2008). Such improvements may potentially help protect investors from the hazards of trading overpriced stocks.…”
Section: Resultsmentioning
confidence: 99%
“…Diether et al (2009b) examined how the SHO regulation affects the market quality. Boulton andBraga-Alves (2009), andBoehmer et al (2008) examined the impact of the short-ban during 2008 global financial crisis and found that the ban on short-selling worsens the market's liquidity and price discovery.…”
Section: The Literature Reviewmentioning
confidence: 99%